En del dör unga: Att minnas de döda genom autoetnografiska analyser - Silow Kallenberg, Kim (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2018)
This article is about personal experience of death and grief. The aim is to gain knowledge on how two mothers talk about losing their adult children, and about their grief. The aim is further to investigate their understandings of why their children died, as it is discussed in relation to the author. Methodologically, an autoethnographic approach is used. An in-depth interview with two grieving mothers is analysed, where the author is also a part of creating the narrative of the two dead men (their sons): Marcus and Noel. The author is also a part of the field in itself, since Marcus and Noel were both her childhood friends. Marcus died while being under treatment in a psychiatric ward. Noel died from an overdose of heroin. Both of their deaths were to some extent unexpected, and definitely untimely. In the article narratives about how they died is presented and analysed. Further, the different explanations to why Marcus and Noel died, expressed in the interview, are discussed. Here the mothers talk about childhood experiences, negative relationships, and substance abuse, as possible explanations to their untimely deaths. Other possible analytical treads to investigate in the empirical material could be protest masculinity, class and affect. These possibilities for further analysis are discussed in the final part of the article.